2007
DOI: 10.1007/s11575-007-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the concentration of US MNE activity: Is it global, regional or national?

Abstract: and Key Results■ Several recent papers by Rugman and his colleagues have improved our understanding of the regional concentration in the activities of the world's largest 500 MNEs. The current paper extends this literature in two dimensions. First, a formal statistical analysis is undertaken to test whether patterns of US MNE assets, sales, income, and employment are consistent with a transactions cost interpretation. Second, this paper allows for the national dimension, defined as activities inside the home c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 31 publications
3
40
0
Order By: Relevance
“…of the 83 per cent intra-regional sales for the home region oriented exporters, 62 per cent never cross the UK border. These observations indicate that the regional concentration is mainly driven by the national dimension of the firm's sales (Hejazi, 2007). The significant share of home sales (over 60%) re-emphasise the critical importance of the national dimension for any international corporate strategy, as it reflects the nature of the firm's FSAs and the associated degree of liability of foreignness (Rugman and Verbeke, 2007).…”
Section: Regional Nature Of the British Exportersmentioning
confidence: 84%
See 2 more Smart Citations
“…of the 83 per cent intra-regional sales for the home region oriented exporters, 62 per cent never cross the UK border. These observations indicate that the regional concentration is mainly driven by the national dimension of the firm's sales (Hejazi, 2007). The significant share of home sales (over 60%) re-emphasise the critical importance of the national dimension for any international corporate strategy, as it reflects the nature of the firm's FSAs and the associated degree of liability of foreignness (Rugman and Verbeke, 2007).…”
Section: Regional Nature Of the British Exportersmentioning
confidence: 84%
“…In a number of subsequent articles and books Rugman and his co-authors have presented considerable empirical evidence on the predominantly home region orientation of the world's largest multinational enterprises (MNEs) (e.g. Rugman and Verbeke, 2004, 2007Rugman, 2005). A formal model in the form of regionalization theory has been put forward intended to explain why firms' international activities are significantly constrained to the home region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While FDI flows and stocks are perfectly appropriate measures of a country's inflows and outflows of financial capital, and of their cumulative size, they are not simply noisy but are biased measures of the magnitude of the value-adding activities performed by MNEs abroad. A number of scholars, including Hejazi (2007), Rangan (1998), and Slangen and Beugelsdijk (2010), have shown that it is possible to use other measures of the aggregate value-adding activity performed by MNE affiliates in host countries to ascertain its magnitude, determinants, or impact on host countries. We believe the time has come for others in the IB field to follow their lead.…”
Section: Models 3a and 3b Inmentioning
confidence: 99%
“…Anderson, 2011 ) and more recently foreign direct investments (e.g. Hejazi, 2007 ), including those in banking ( Claessens and Van Horen, 2014b ).…”
Section: Discussionmentioning
confidence: 99%